Doryphagy: when selective autophagy safeguards centrosome integrity. (3rd March 2020) - Cianfanelli, Valentina; Cecconi, Francesco
ABSTRACT: Although centrosome abnormalities are frequent in cancer, the mechanisms responsible for their accumulation are poorly understood. Here we comment on our recent publication identifying a new type of selective autophagy, named doryphagy, which preserves centrosome organization through targeting Centriolar Satellites (CS). Thus, doryphagy prevents inaccurate mitosis and genomic instability.